Алгебро-алгоритмические средства проектирования знаний предметных областей - Цейтлин, Г.Е.; Захария, Л.М. (Кибернетика и системный анализ, 2009)
Розвинуто теорію клонів у напрямку формалізації алгоритмічних знань в предметних областях. Коротко представлено клон Поста, алгоритмічні клони Дейкстри, Глушкова, граф-схеми Калужніна, клон Кліні регулярних виразів, а також клон Кодда n-відношень з різними операціями суперпозиції. Клон n-відношень формалізує проектування задач, для яких характерна обробка великих структурованих об’ємів інформації. За модельний приклад взято економічні застосування. The paper develops the clone theory to formalize algorithmic knowledge in subject areas. The Post clone, algorithmic clones of Dijkstra, Glushkov, and Kalygnin graph schemes, and Clini’s clone of regular expressions are briefly outlined and Codd’s clone of n-relations with different operations of superposition are described. The n-relation clone is used to formalize scientific problems that process large volumes of structured information. Economic applications are taken as model examples.